Anti-oxidation performance of carbon aerogel composites with SiCO ceramic inner coating. Issue 8 (1st June 2019) - Li, Xiafei; Feng, Junzong; Jiang, Yonggang; Li, Liangjun; Feng, Jian
Abstract: To improve the oxidative-resistant ability of carbon fibre-reinforced carbon aerogel composites (C/CAs), C/CAs were impregnated with a silicon oxycarbide (SiCO) precursor sol several times. After gelating, aging, solvent exchanging, ambient drying, and pyrolyzing, the SiCO precursor sol infiltrated the nanoporous C/CA, and anti-oxidation carbon aerogel composites with a SiCO ceramic inner coating (C/CA-SiCO) were prepared. It was found that the density of the material increases with the number of times that impregnation and pyrolysis were carried out. The mechanical properties and the anti-oxidant performance were significantly improved after the deposition with different numbers of the SiCO coating cycles. The bending strength increased from 2.2 MPa to 10.8–32.3 MPa and the compressive strength (10%ε) increased from 0.4 MPa to 3.6–44.4 MPa. The weight loss for the as-prepared composites after heating at 1600 °C for 60 min in air was only 7.6%, and the in-plane shrinkage was less than 2%. Additionally, after the oxidation resistance test, the surface of the C/CA-SiCO had abundant β-SiO2 crystalline, whereas its inner region of the composite remained amorphous.